Religion and Politics: Symbolization of Religion in the contestation of legislative elections 2019 - Amar Muhyi Dinis Sipa; Hopizal Wadi; Fahrurrazi Fahrurrazi (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2021)
Politics and religion have become inseparable these days. Politicians or political parties' piety and religiosity have become a necessity. A Strong religion as a doctrine, even politics, requires religion as a tool of legitimacy to achieve existence, power and attract votes and sympathy from the masses. Finally, spirituality and religious symbols become political products and domains that become the identity of politicians and political parties and are then introduced to the public, known as political marketing. This article aims to understand further political discourse with religious symbolic packaging on PKS candidate posters used as campaign tools to influence public choice. The approach in this article uses semiotic analysis to analyze the symbols in the political campaign posters of candidates on social media. So, Semiotics tries to dismantle signs that have meaning in social life and political life. The method used in this article is a qualitative method that is descriptive-analytical, with a data collection technique analyzing campaign posters on Instagram social media on the @pkstangerang account. The result of this article is that religious politics exists because of the role of religion that can touch the emotional side of humans. In the account @pkstangerang, most of his posts are inseparable from religious spirituality and religious doctrine elements. While campaigning in legislative elections also can not be separated from religious symbols and narratives or symbols of piety, for example, candidates who wear peci, koko clothes, and hold the book of fiqh. For this reason, the term religious politics in politics or legislative elections is a religious campaign term that describes religiosity in politics as a way of political marketing.